Ginkgo Biloba Extract EGB761 Ameliorates the Extracellular Matrix Accumulation and Mesenchymal Transformation of Renal Tubules in Diabetic Kidney Disease by Inhibiting Endoplasmic Reticulum Stress. (23rd March 2021) - Han, Jiarui; Pang, Xinxin; Shi, Xiujie; Zhang, Yage; Peng, Zining; Xing, Yufeng
Abstract : The study is aimed at investigating the effects of Ginkgo biloba extract EGB761 on renal tubular damage and endoplasmic reticulum stress (ERS) in diabetic kidney disease (DKD). A total of 50 C57BL/6 N mice were randomly divided into the normal group, DKD group, DKD+EGB761 group (36 mg/kg), and DKD+4-phenylbutyrate (4-PBA) group (1 g/kg). The DKD model was replicated by high-fat diet combined with intraperitoneal injection of streptozotocin (STZ). Renal tubular epithelial cells (HK-2) were divided into the control group, high-glucose group (30 mmol/L), EGB761 group (40 mg/L, 20 mg/L, 10 mg/L), TM group, and TM+4-PBA group. After 8 weeks of administration, expressions of serum creatinine (Scr), blood urea nitrogen (BUN), 24 h urinary protein (24 h Pro), fasting blood glucose (FBG), β 2 -microglobulin ( β 2 -MG), and retinol binding protein 4 (RBP4) of mice were tested. The pathological changes of renal tissue were observed. The expressions of extracellular matrix (ECM) accumulation and epithelial-mesenchymal transition (EMT) markers α -smooth muscle actin ( α -SMA), E-cadherin, fibronectin, and collagen IV, as well as the ERS markers GRP78 and ATF6, were tested by Western blot, qPCR, immunohistochemistry, or immunofluorescence. EGB761 could decrease the Scr, BUN, 24 h Pro, and FBG levels in the DKD group, alleviate renal pathological injury, decrease urine β 2 -MG, RBP4 levels, and decrease the expression of α -SMA, collagen IV, fibronectin, and GRP78, as well as ATF6, while increase the expression of E-cadherin. These findings demonstrate that EGB761 can improve renal function, reduce tubular injury, and ameliorate ECM accumulation and EMT in DKD kidney tubules, and the mechanism may be related to the inhibition of ERS.